2021
DOI: 10.1037/sgd0000521
|View full text |Cite
|
Sign up to set email alerts
|

Relationship functioning of sexual minority people of color.

Abstract: Over the past 10 years, research on sexual minority (SM) or same-sex/gender couples has increased. However, this research has largely reflected White SM couples' experiences via majority White SM participant samples. To highlight the dearth of scholarship on Sexual Minority People of Color (SMPOC) in relationship research, this article provides a review and critique of the empirical literature from January 2010 to June 2020 on the factors associated with romantic relationship functioning among SMPOC. Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Tornello (2021) took a critical approach and specifically examined relationship functioning for sexual minority persons of color. Utilizing a rigorous method of systematically reviewing scholarship published between 2010 and 2020, Tornello found that much of the extant knowledge base to date has used predominantly white samples.…”
Section: Organization and Content Of The Special Issuementioning
confidence: 99%
“…Tornello (2021) took a critical approach and specifically examined relationship functioning for sexual minority persons of color. Utilizing a rigorous method of systematically reviewing scholarship published between 2010 and 2020, Tornello found that much of the extant knowledge base to date has used predominantly white samples.…”
Section: Organization and Content Of The Special Issuementioning
confidence: 99%
“…An important new addition to the updated Guidelines (APA, 2021) is Guideline 8, which emphasizes the importance for psychologists to recognize positive aspects of being a sexual minority, including individual and collective resilience. In line with this new guideline, Tornello’s (2021) careful systematic review and critical evaluation of the available literature offers a refreshing pivot from the standard deficit model we have seen over the past few decades. This approach typically focuses on risk profiles of sexual minority communities, overlooking the resilience, strength, and innovation of sexual minority people—especially those who live at the intersection of multiple marginalized identities (Huang et al, 2010).…”
mentioning
confidence: 94%
“…Psychologists should make sure to read Guideline 8, and consider ways of utilizing resilience-based intervention to enhance relationship functioning among sexual minority persons of color in romantic relationships. Tornello's (2021) work recognizes the importance of parenting among sexual minority persons of color, which aligns with Guideline 12 (APA, 2021). Psychologists should be aware that there is an overall lack of research and scholarship on the romantic relationships of sexual minority persons of colors within the context of family systems, including stages and roles of family development (e.g., transition to parenthood, child rearing and launching, etc.).…”
mentioning
confidence: 98%
See 2 more Smart Citations